2001
DOI: 10.1590/s0101-81752001000500032
|View full text |Cite
|
Sign up to set email alerts
|

Nota complementar sobre a composição ictiofaunística da Baía de Guaratuba, Paraná, Brasil

Abstract: ABSTRACT. A complemcntary note about the icthyofaunistic composition ofthe Guaratuba Bay, Paraná, Brazil. The utilisation of Illultiple gears and the surveying of olher areas lhan that of Illangrove habitats have increased in 27 the nUlllber of fish species known in the Guaratuba Bay, an esluarine ecosystelll located in the southern of Brazilian coastal region (2S 0 S2 'S, 48°39'W). The new occurrence of a typically freshwater species (Pimelodidae) and of several Clupeifolmes and Gobiidae species, reveals the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 4 publications
0
13
1
6
Order By: Relevance
“…The high frequencies of mature females in the spring and summer and the high values of the Gonadossomatic index and of the Gonadal Condition factor in these seasons, indicated that the reproductive period of the species occured at this time. As females with emptied ovaries were not found in the present study, and because the species was not found in shallower areas than those of the present study (Godefroid, 1997(Godefroid, , 2002Corrêa, 1987;Chaves and Corrêa, 1998;Chaves and Vendel, 2001), it was possible that spawning occured at depths more than 15 meters. More studies on the biology of C. bleekerianus, as well as of other species of Clupeiformes, are necessary for a better understanding of the ecosystems where they occur, since they are, as a rule, abundant species.…”
Section: Discussioncontrasting
confidence: 55%
“…The high frequencies of mature females in the spring and summer and the high values of the Gonadossomatic index and of the Gonadal Condition factor in these seasons, indicated that the reproductive period of the species occured at this time. As females with emptied ovaries were not found in the present study, and because the species was not found in shallower areas than those of the present study (Godefroid, 1997(Godefroid, , 2002Corrêa, 1987;Chaves and Corrêa, 1998;Chaves and Vendel, 2001), it was possible that spawning occured at depths more than 15 meters. More studies on the biology of C. bleekerianus, as well as of other species of Clupeiformes, are necessary for a better understanding of the ecosystems where they occur, since they are, as a rule, abundant species.…”
Section: Discussioncontrasting
confidence: 55%
“…This is supported by Andrade-Tubino et al (2008) that state such families among the most important in Brazilian coast, and by Vieira & Musick (1994), which reveal them as the most conspicuous in SW Atlantic estuarine fish assemblages. Carangidae and Sciaenidae were also the two most speciose families in the two large estuaries near the PEC, the Guaratuba Bay, located just south of the PEC, and the Babitonga Bay, located 70 Km south of the PEC (Chaves & Corrêa 1998, Chaves & Vendel 2001, Vilar et al 2011. Anchoa and Cynoscion had six species each and were the richest genera in the PEC.…”
Section: Resultsmentioning
confidence: 99%
“…A composição ictiofaunística da foz do Rio Itajaí-Açu é menor do que encontrada em outros estudos semelhantes realizados na costa sul do Brasil, nos quais se verificou um nú-mero bastante alto de espécies (Chao et al, 1982;Chaves & Vendel, 2001). A presença nas capturas de exemplares das famílias Gerreidae e Carangidae no rio Itajaí-Açú, reforça as conclusões dos levantamentos de ictiofauna realizados anteriormente em outros ambientes estuarinos, tais como o manguezal de Itacorubi (Soriano-Sierra & Sierra de Ledo, 1998) e o manguezal do Rio Camboriú (Rodrigues et al, 1994).…”
Section: Discussionunclassified